Continuous flow microwave system with helical tubes for liquid food heating. (April 2021) - Zhang, Yuhao; Yang, Huayu; Yan, Bowen; Zhu, Huaping; Gao, Wenhua; Zhao, Jianxin; Zhang, Hao; Chen, Wei; Fan, Daming
Abstract: The structural parameters of tubes (straight or helical tubes) might affect the heating liquid foods in continuous flow microwave system. Therefore, the objectives were to build a mathematical model for continuous flow microwave heating system with helical tubes for liquid foods heating. A finite element calculation was used for the model, and distilled water, as a representative of liquid foods, was used to validate experimentally and numerically. This model was employed to analyze the liquid heating efficiency with different pitch circle diameters (PCDs), tube diameters, and screw pitches of helical tubes. The heating efficiency was affected by electromagnetic power density distribution, secondary flow intensity, and dielectric properties of heated fluid. Furthermore, the optimal heating efficiency with these variations were given. This study is expected to provide advice to enhance the heating efficiency of liquid foods in design and optimization studies for continuous flow microwave system. Highlights: A continuous flow microwave system with helical tubes was proposed. A generic complete numerical model of this system was developed. The liquid heating efficiency was analyzed by electromagnetism and fluid mechanics. High electromagnetic hotspots occured between adjacent tube walls. The microwave wavelength and screw pitch affected the microwave energy utilization.